2010
DOI: 10.1108/14691931011013325
|View full text |Cite
|
Sign up to set email alerts
|

Analysing value added as an indicator of intellectual capital and its consequences on company performance

Abstract: Purpose -The purpose of this paper is to analyse the role of value added (VA) as an indicator of intellectual capital (IC), and its impact on the firm's economic, financial and stock market performance. Design/methodology/approach -The value added intellectual coefficient (VAICe) method is used on 300 UK companies divided into three groups of industries: high-tech, traditional and services. Data require to calculate VAICe method are obtained from the "Value Added Scoreboard" provided by the UK Department of Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
392
4
24

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(461 citation statements)
references
References 35 publications
41
392
4
24
Order By: Relevance
“…Almost all the prior studies on IC over the last two decades for example (Anuonye, 2015;Lina, 2014;Sledzik, 2013;Kamal et al, 2011, Zeghal andMaaloul, 2010) are mostly concentrated on banking and financial sectors and neglect other sectors, food product companies inclusive. Still they do not reach any agreement on the role of firm's performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almost all the prior studies on IC over the last two decades for example (Anuonye, 2015;Lina, 2014;Sledzik, 2013;Kamal et al, 2011, Zeghal andMaaloul, 2010) are mostly concentrated on banking and financial sectors and neglect other sectors, food product companies inclusive. Still they do not reach any agreement on the role of firm's performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, results that obtained by Zéghal, Anis Maaloul, (2010) show that intellectual capital efficiency has a positive effect on financial performance of company. In Maditinos,D et al study (2011), the relation between intellectual capital and return on equity rate confirmed and this is conforming to our results in present study.…”
Section: Conclusion and Suggestionsmentioning
confidence: 95%
“…Research history Zéghal and Maaloul (2010) measured the intellectual capital by added-value index and studied its effect on financial, economical and market value performance of 300 Britain's companies. For measuring the intellectual capital, they used the intellectual added-value coefficient.…”
Section: IIImentioning
confidence: 99%
“…Empirical research refers to a knowledge-base as the core competence of enterprises. Through creating competitive advantages and increasing the book value of intangible assets denoted as intellectual capital, there is more evidence to support positive relations with firm performance (Mavridis, 2004;Youndt & Snell, 2004;Goh, 2005;Zeghal & Maaloul, 2010;Cheng et al, 2010). Intellectual capital is based employees' knowledge, expertise, and skills and is used to create trademarks or patents.…”
Section: Review Of Literaturementioning
confidence: 99%